Analisis Tingkat Kesesuaian Aplikasi Simba Baznas Dengan PSAK 109 Pada Baznas Kota Ternate - Hamid, Murniyati; Rosdiana, Rosdiana; Ruray, Titiek Arafiani (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the level of conformity between the implementation of the SIMBA (BAZNAS Management Information System) application and the Statement of Financial Accounting Standards (PSAK) 109 concerning Zakat, Infak, and Sedekah (ZIS) at BAZNAS Ternate City. The research method used is qualitative with a case study approach through observation, interviews, and documentation. The results show that the process of collecting and distributing ZIS at BAZNAS Ternate City is in accordance with PSAK 109 provisions, particularly in the recognition, measurement, presentation, and disclosure of transactions. The financial reports generated by SIMBA are also consistent with PSAK 109 as they present the five main components, namely the statement of financial position, cash flow statement, statement of changes in funds, statement of changes in managed assets, and notes to the financial statements, including the separation of zakat, infak, and sedekah (ZIS) funds. However, there are several limitations, such as the absence of PSAK 109 application in cases of non-cash zakat in the form of fixed assets, as well as the management of infak/sedekah funds in the form of revolving fund enterprises. This study suggests that the central BAZNAS continue to update SIMBA features, BAZNAS Ternate City improve the competence of SIMBA management human resources, and strengthen transparency through regular publication of financial reports.